It influences of the sociocultural factors in the buccal health of women in fertile age of the rural community of Mala - Campodónico Reátegui, Carlos (2006)
The purpose of this study is to determinate the influence of the sociocultural factors in the oral health of Women in Fertile Age (WFA) in Mala's rural comunnity on 2004. For this study we take a research group of 40 WFA of Mala cornmunity (from 15 to 49 years old) who were selected according to the selection criterion established for the present study. To these women we practice a structure survey according to the research variable and then we practice a dental examination to corroborate the oral health state we also take DMFT index of every one. We found a strong influence of the Number of children's factor with 9 significative differences following the factors age, instruction degree, civil state, work and violence against women all of them with same significative differences. In fact, the sociocultural factors have a great influence in the oral health state of women in fertile age of Mala's rural community being the number of children's, the factor with more influence.